Theorizing Transformative Education: An Exploration into Marcuse’s Aesthetic Dimension - Adrienne Pickett (Adult Education Research Conference, 2016)
In this paper, I propose that the underlying quality of transformation is what Herbert Marcuse calls the aesthetic dimension. I use aesthetic language to understand better the nature of transformative education.
Keywords: transformative education; adult learning; aesthetics; philosophy